A study on the solid-state welding of boron-doped Ni3Al-AISI 304 stainless steel couple - Yidirim, S; Kelestemur, MH (Elsevier, 2005)
The solid-state welding of boron-doped Ni3Al intermetallic compound with AISI 304 austenitic stainless steel has been carried out. The interface characteristics of bonding have been examined by using SEM, EDS and XRD. The elasto-plastic analyses on the interface zones of the bonds have been conducted to obtain residual stress induced by different thermal expansion properties of bonded materials. The results indicate that, since ignorable level of brittleness occurs, and a reasonable thermal expansion exists on the interface zone of Ni3Al and 304 stainless steel couple, the zone of diffusion welding practiced between Ni3Al intermetallic compound and AISI 304 austenitic, stainless steel is safe from the point of micro-structural and thermal expansion induced failures. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: solid-state welding; Ni3Al+B; AISI 304; diffusion; intermetallic alloys and compounds